2019
DOI: 10.1016/j.pulmoe.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Krebs von den Lungen-6 associated with chest high-resolution CT score in evaluation severity of patients with interstitial lung disease

Abstract: Serum KL-6 might be useful in the diagnosis of ILD, especially in the hard-to-diagnose cases, with high sensitivity and specificity. Furthermore, KL-6 might be a valuable marker for evaluation of ILD severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
3
18
0
2
Order By: Relevance
“…In this work, there is a significant negative correlation between KL-6 level and oxygen saturation, PaO 2 , and FVC. This was consistent with a study by Qin et al that reported a decrease in O 2 saturation and lung functions in patients with elevated KL-6 levels [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this work, there is a significant negative correlation between KL-6 level and oxygen saturation, PaO 2 , and FVC. This was consistent with a study by Qin et al that reported a decrease in O 2 saturation and lung functions in patients with elevated KL-6 levels [22].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Qin et al's study also reported that KL-6 levels in ILD were significantly higher than pneumonia, other types of parenchymal diseases (P < 0.000), and healthy controls (P < 0.05) [22].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A study of 47 patients with rheumatoid arthritis-associated pulmonary disease by Kinoshita et al also reported a positive correlation between serum KL-6 levels and total CT scores (r = 0.83, P < 0.001) [38]. In addition, a study of 98 patients with ILD by Qin et al showed that serum KL-6 levels were significantly correlated with DL CO (r = -0.513, P < 0.001) and CT scores (r = 0.539, P = 0.000) [39]. These results support that serum KL-6 levels may correlate with the severity of ILDs.…”
Section: Plos Onementioning
confidence: 94%
“…The disease severity is highly variable according to the underlying condition but unfortunately, children with CLD have high overall morbidity and mortality [2]. Therefore, it is very important to find a non-invasive blood biomarker that could help in the diagnosis and predict the prognosis of ILD, it would be of more value in areas with limited resources to allow easier and earlier detection of more vulnerable patients [3].…”
Section: Introductionmentioning
confidence: 99%